The exploration of Indonesian students’ attributions in EFL reading and writing classes - Yustinus Calvin Gai Mali (Fakultas Sastra Universitas Negeri Malang, 2022)
The exploration of Indonesian students’ attributions in EFL reading and writing classesAlthough the previous studies have given so much attention to exploring the students’ attributions in various settings and academic levels, there is a scarcity of research that presents and compares findings on the attributions of Indonesian university students, specifically in the reading (receptive skill) and writing (productive skill) courses. This study researched students’ attributions in their English as a Foreign Language (EFL) writing and reading classrooms at a private university in Indonesia. The research participants were 161 students who responded to an online questionnaire that explored their attributions for the success or failure in achieving the learning objectives of the classes. The study revealed that most of the students in both courses could successfully achieve the learning objectives, and there were no attribution differences in the courses. Their effort and positive teacher’s performances were mostly cited attributions for the success, whereas low ability and lack of effort were the primary attributions for some students’ failure in achieving the learning objectives of the classes. Practical strategies to support teaching and learning in the EFL reading and writing classes and directions for further research were presented.Keywords: attribution, EFL teaching, reading, writingEksplorasi atribusi mahasiswa Indonesia di kelas menulis dan membaca bahasa Inggris sebagai bahasa asingMeskipun penelitian sebelumnya telah banyak mengeksplorasi atribusi siswa di tempat dan tingkat pendidikan yang berbeda, masih sedikit penelitian yang menyajikan dan membandingkan hasil kajian atribusi dari para mahasiswa Indonesia, khususnya di kelas membaca (kemampuan reseptif) dan menulis (kemampuan produktif). Kajian ini meneliti atribusi para mahasiswa di kelas menulis dan membaca bahasa Inggris sebagai bahasa asing (EFL) di salah satu universitas swasta di Indonesia. Subjek penelitian ini adalah 161 mahasiswa. Mereka mengisi kuesioner secara online yang mengeksplorasi atribusi tentang keberhasilan dan kegagalan mereka untuk mencapai tujuan pembelajaran di dalam kelas. Hasil penelitian menunjukan bahwa mayoritas mahasiswa merasa dapat mencapai tujuan pembelajaran dengan sukses, dan tidak ada perbedaan atribusi di kedua kelas tersebut. Usaha dan performa positif guru mereka menjadi atribusi yang banyak disebutkan oleh para mahasiswa untuk keberhasilannya, sedangkan tingkat kemampuan yang rendah dan kurangnya usaha menjadi atribusi utama yang menjelaskan tentang kegagalan beberapa mahasiswa untuk mencapai tujuan pembelajaran di dalam kelas. Strategi praktikal untuk mendukung pengajaran dan pembelajaran di kelas membaca dan menulis EFL tersebut, dan petunjuk untuk penelitian selanjutnya juga dibahas.Kata kunci: atribusi, pengajaran EFL, membaca, menulis